Research on Governance of Enterprise Investment and Financing Contract Based on the Universality of Data Assets - Li, Ping (Education Insights, 2026)
This study investigates corporate investment and financing contract governance from the perspective of data asset universality, combining theoretical analysis with real-world case observations to clarify how the widespread applicability, shareability, and standardization of data assets reshape contractual governance mechanisms. It analyzes how the universal characteristics of data assets influence the design, optimization, and enforcement of contract terms in investment and financing arrangements. The findings indicate that data asset universality plays a critical role in improving the precision of contract clauses, mitigating information asymmetry between participating parties, and enhancing the efficiency and reliability of contract execution processes. By enabling more transparent data flows, standardized evaluation metrics, and verifiable performance indicators, data asset universality supports more rational decision-making and strengthens trust among stakeholders. Based on these insights, the study proposes practical governance strategies that integrate data-driven monitoring, dynamic adjustment mechanisms, and standardized data utilization frameworks to promote more sustainable, efficient, and resilient corporate investment and financing practices in the digital economy.